2014
DOI: 10.1039/c4cc03565h
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and practical synthesis of 3-oxyindoles through gold-catalyzed intermolecular oxidation of o-ethynylanilines

Abstract: A novel gold-catalyzed intermolecular oxidation of o-ethynylanilines has been developed. A range of functionalized 3-oxyindoles are readily accessed by utilizing this strategy. Importantly, this gold-catalyzed oxidative process outcompetes the typical indole formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…In summary, by utilizing the steric strain in ring formation to achieve the control of regioselectivity, a variety of gold-catalyzed anti-Markovnikov cycloisomerization-initiated tandem reactions have been developed, providing a facile and efficient way for the construction of various synthetically useful heterocycles, especially the optically active N-heterocycles by combining the chiral tert-butylsulfinimine chemistry and gold catalysis [65][66][67][68][69][70][71][72][73][74][75]. In our opinion, this study will continue to be a very exciting area for the expedient synthesis of valuable heterocycles [76].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, by utilizing the steric strain in ring formation to achieve the control of regioselectivity, a variety of gold-catalyzed anti-Markovnikov cycloisomerization-initiated tandem reactions have been developed, providing a facile and efficient way for the construction of various synthetically useful heterocycles, especially the optically active N-heterocycles by combining the chiral tert-butylsulfinimine chemistry and gold catalysis [65][66][67][68][69][70][71][72][73][74][75]. In our opinion, this study will continue to be a very exciting area for the expedient synthesis of valuable heterocycles [76].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, we reported that highly electrophilic α‐oxo gold carbene intermediates could be generated by intermolecular oxidation of benign alkynes instead of from hazardous diazo ketones (Scheme B) . The safety benefit of this strategy and the new approach to α‐oxo gold carbenes and their novel chemistry spurred a diverse range of subsequent studies by us and others, and established that the gold carbene intermediates, or in some cases their precursors, can undergo insertions into O−H, N−H, B−H, and even unactivated C−H bonds,, and cyclopropanate alkenes,,, including electron‐deficient ones, as well as undergo electrophilic arene substitutions or Buchner reactions, and the formation of ylides . Despite these advances, no Wolff‐type rearrangement involving these oxidatively generated α‐oxo gold carbenes has been reported to date.…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, this protocol circumvents the use of hazardous and potentially explosive diazo carbonyl compounds, and makes alkynes as equivalents of α‐diazo ketones. In our recent study toward such a gold‐catalyzed oxidative cyclization,10 we reported a gold‐catalyzed intermolecular oxidation of o ‐ethynylanilines for the synthesis of synthetically useful 3‐oxyindoles, which outcompetes the typical indole formation 10c. Inspired by these results, we envisioned that the synthesis of 3‐coumaranones might be accessed directly from the corresponding o ‐ethynylphenol substrates by using a similar strategy (Scheme ) 11.…”
Section: Methodsmentioning
confidence: 99%